Posterior mini-incision total hip arthroplasty controls the extent of post-operative formation of heterotopic ossification. - Edwards,DS; Barbur,SAR; Bull,AMJ; Stranks,GJ (Eur J Orthop Surg Traumatol, 2015)
Heterotopic ossification (HO) is the formation of bone at extra-skeletal sites. Reported rates of HO after hip arthroplasty range from 8 to 90 %; however, it is only severe cases that cause problems clinically, such as joint stiffness. The effects of surgical-related controllable intra-operative risk factors for the formation of HO were investigated. Data examined included gender, age of patient, fat depth, length of operation, incision length, prosthetic fixation method, the use of pulsed lavage and canal brush, and component size and material. All cases were performed by the same surgeon using the posterior approach. A total of 510 cases of hip arthroplasty were included, with an overall rate of HO of 10.2 %. Longer-lasting operations resulted in higher grades of HO (p = 0.047). Incisions >10 cm resulted in more widespread HO formation (p = 0.021). No further correlations were seen between HO formation and fat depth, blood loss, instrumentation, fixation methods or prosthesis material. The mini-incision approach is comparable to the standard approach in the aetiology of HO formation, and whilst the rate of HO may not be controllable, a posterior mini-incision approach can limit its extent.